Cetuximab pharmacokinetic/pharmacodynamics relationships in advanced head and neck carcinoma patients. Issue 6 (13th April 2019) - Le Louedec, Félicien; Alix‐Panabières, Catherine; Lafont, Thierry; Allal, Ben C.; Garrel, Renaud; Digue, Laurence; Guigay, Joël; Cupissol, Didier; Delord, Jean‐Pierre; Lallemant, Benjamin; Alfonsi, Marc; Aubry, Karine; et al.
Abstract : Aims: Cetuximab associated with cisplatin and 5‐fluorouracil is used to treat patients with inoperable or metastatic head and neck squamous cell carcinomas (HNSCC) up until disease progression or unacceptable toxicities. To date, no biomarkers of efficacy are available to select patients who will benefit from treatment. Methods: An ancillary pharmacokinetics (PK) exploration was performed in the context of a prospective study investigating circulating‐tumour cells vs progression‐free survival (PFS). Cetuximab plasma concentrations were analysed according to a population PK model. Individual exposure parameters were confronted with soluble epidermal growth factor receptor (sEGFR) concentrations, tumour response and PFS. Results: PK data (28 patients, 203 observations) were best described by a two‐compartment model with linear elimination. Performance status (PS) significantly correlated to both cetuximab clearance and central volume of distribution with both parameters increasing by 33.3% (95% CI 1–65.6) for each 1‐point increase of PS compared to PS = 0. Univariate analysis showed that patients with higher trough cetuximab concentrations at Day 7 (Cmin, D7 ) had better tumour response ( P = 0.03) and longer PFS ( P = 0.035). However, multivariate analysis revealed that only PS and tumour size at baseline remained significantly associated with PFS. Levels of sEGFR increased during cetuximab treatment but were not associated with PFS in the multivariate analysis. Conclusions: Our study prospectively indicates that PS is likely a confounding factor in the relationship between cetuximab PK and PFS, patients with a poor PS having lower cetuximab plasma exposure and lower PFS.